2000
DOI: 10.1023/a:1026579623136
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar soft part sarcoma in children and adolescents: A report from the Soft-Tissue Sarcoma Italian Cooperative Group

Abstract: SummaryBackground: Alveolar soft part sarcoma (ASPS) is a rare malignant tumor and little is known about its clinical features and management. We report on a series of 19 pediatric patients managed over 20 years.Patients and methods: Primary conservative surgery was performed in all patients and was radical in nine, non-radical in three; seven patients underwent biopsy alone (3 unresectable tumors, 4 metastatic disease). In two cases radical surgery was performed after primary chemotherapy. Radiotherapy was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
163
4
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(185 citation statements)
references
References 12 publications
15
163
4
3
Order By: Relevance
“…We found age older than 75+ years independently predicted poor survival. Moreover, as reported by Casanova et al [7], we also found younger age did not predict improved survival.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We found age older than 75+ years independently predicted poor survival. Moreover, as reported by Casanova et al [7], we also found younger age did not predict improved survival.…”
Section: Discussionsupporting
confidence: 87%
“…This observation has been confirmed by others [7,8,39]. However, Ross et al [36] reported no association of primary tumor site with patient survival.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Studies are underway to evaluate the utility of sentinel lymph node biopsy [28,29]. The indication for nodal biopsy in cases of NRSTS affecting the extremities is more controversial: some histotypes (i.e., epithelioid sarcoma, clear cell sarcoma, alveolar soft part sarcoma, and angiosarcoma) would appear to have a greater tendency than others to spread to regional lymph nodes, and biopsy may be indicated in such cases [21,27], though pediatric cases seem to have a weaker propensity for nodal spread than in their adult counterpart (particularly for epithelioid sarcoma [30]) so further studies are needed to clarify this matter. Of course, good coordination between surgeon, pediatric oncologist, pathologist, and radiotherapist is mandatory to plan a successful multimodality treatment for these patients, and the pediatric oncology team should also consider procedures such as regional arterial perfusion [31,32] or intraoperative brachytherapy, which are generally used more for adult STS of the extremities but may have a role in some specific pediatric cases.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate prognosis is still poor. There is only a partial response on chemotherapy in various combinations, in about 30% (Casanova et al, 2000;van Ruth et al, 2002).…”
mentioning
confidence: 99%